Project Masiluleke : texting and testing to fight HIV/AIDS in South Africa - Canales, Rodrigo, (SAGE Knowledge. Cases., 2017)
When Krista Dong and Zinhle Thabethe came to the 2006 PopTech conference in Camden, Maine, they hoped to expand their fight against HIV/AIDS, one of South Africas greatest problems. They were the founders of iTEACH, an HIV/AIDS and TB prevention and treatment program in KwaZulu-Natal, South Africa. Impressed by their story, conference organizers and Robert Fabricant of frog design came together with iTEACH to address these real-world challenges through the conferences vision accelerating social innovation through technology.